Performance of a Leaf-Galling Phylloxera (Daktulosphaira vitifoliae) on Roots of Diverse Vitis spp. Rootstocks in North East Victoria, Australia - C. W. Clarke; K. S. Powell; S. Norng; B. M. Carmody; M. Walpole; J. P. Cunningham (Australian Journal of Grape and Wine Research)
Background and Aims. Grape phylloxera in Australia comprises diverse genetic strains that feed on roots and leaves of Vitis spp. The G38 phylloxera strain was detected on roots of Vitis spp., for the first time in North East Victoria in 2015. Prior to 2015, G38 phylloxera was only known to feed on leaves. The aim of this study was to evaluate the survival and development of G38 phylloxera on roots of diverse Vitis spp. under field, controlled laboratory, and greenhouse conditions. Methods and Results. In the field, emergence traps quantified first instars and alates emerging from roots of diverse rootstocks and Vitis vinifera L. High numbers of phylloxera were collected in traps placed at vines of rootstocks 101-14, 3309 Courderc and Schwarzmann. Nodosity were also observed on roots of 101-14, 3309 Courderc and Schwarzmann in the field and in-pot vines experiments. The better performance of G38 phylloxera on these three rootstocks compared to V. vinifera in the field and in potted vines parallelled the excised roots experiments. Conclusions. The relatively high performance of G38 phylloxera on the 101-14, 3309 Courderc and Schwarzmann rootstocks suggest a susceptible response and could be associated with rootstock parentage. Further investigation is warranted to determine implications for rootstocks development. Significance of the Study. These findings are fundamental for decision-making in phylloxera risk assessment and rootstock selection. The study reaffirms the need for triphasic (in vitro, in planta, and in-field) rootstock screening protocols for phylloxera.